Technological innovation, trade openness, natural resources, clean energy on environmental sustainably: a competitive assessment between CO2 emission, ecological footprint, load capacity factor and inverted load capacity factor in BRICS+T - Sun, Jie; Qamruzzaman, Md. (Frontiers in Environmental Science, 2025)
The study investigates the relationship between technological innovation, clean energy, trade openness, and natural resource rents on environmental sustainability within BRICS + T nations. Motivated by the urgent need to address escalating CO2 emissions—reaching 36.4 billion metric tons in 2022—the research aims to understand how these factors influence CO2 emissions, ecological footprint, load capacity factor, and its inverse, contributing to the Sustainable Development Goals (SDGs). The study uses panel data from BRICS + T countries spanning the period from 1990 to 2022. Employing advanced econometric techniques such as Dynamic Seemingly Unrelated Regression (DSUR), Cross-Sectionally Augmented Panel Unit Root (CUP-FM, CUP-BC), and nonlinear autoregressive distributed lag (ARDL) models, the research tests the Environmental Kuznets Curve (EKC) hypothesis and evaluates asymmetric effects of the variables. Key findings indicate that technological innovation consistently reduces CO2 emissions and ecological footprints, reinforcing its role in promoting sustainability through cleaner technologies and more efficient industrial processes. Clean energy adoption has also been shown to be a significant driver in reducing environmental degradation, with consistent negative effects on emissions and ecological footprint, while improving the load capacity factor. However, trade openness exhibits a dual effect. While it enhances resource use efficiency, it simultaneously increases CO2 emissions and the ecological footprint, likely due to heightened industrial activity. Natural resource rents display mixed results: in some cases, they exacerbate emissions, while in others, they contribute to sustainability by funding eco-friendly initiatives. The study recommends that BRICS + T nations prioritize investments in green technologies, strengthen environmental regulations, and enhance international collaboration to accelerate the transition to renewable energy. Policymakers should balance the benefits of trade openness with stricter environmental standards to mitigate its adverse effects on sustainability. These integrated strategies are essential for achieving the environmental targets outlined in the SDGs.